PENGARUH TINGKAT KEPERCAYAAN DAN KUALITAS PRODUK TERHADAP LOYALITAS NASABAH PADA PT. PEGADAIAN UNIT MANISA CABANG RAPPANG - Paradina, Vira; Fatimah, Fatimah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to examine the effect of the level of trust and product quality on customer loyalty. The regression test results for the variable trust in customer loyalty show the number of t count = 2.191 with a significance value of 0.032. Using the value of t table = 1.665, the value of t count> t table (2.191> 1.665) so it can be concluded that it has a positive effect. (hypothesis is accepted). Thus the variable trust has a significant effect on customer loyalty at PT. Pegadaian Unit Manisa, Kabupaten Rappang. The result of regression testing for the variable Product Quality to Customer Loyalty shows the number of t count = 4.112 with a significance value of 0.000. Use the value of t table = 1.665. Then the value of t count> t table (4.112> 1.665) so that the hypothesis is accepted. Thus product quality has a significant effect on customer loyalty at PT. Pegadaian Unit Manisa, Kabupaten Rappang.